Fiscal Indulgence in Central Europe : Loss of the External Anchor - Kopits, George (IMF Working Papers; Working Paper ;, 2004)
In recent years, fiscal performance in Central Europe has steadily deteriorated, in contrast to the improvement in the Baltics. This paper explores the determinants of such differences among countries slated for EU accession. Regression estimates suggest that economic and institutional fundamentals do not provide a full explanation. An alternative explanation lies in the political economy of the accession process, and a game-theoretic model illustrates why a country with a stronger bargaining position might have an incentive to deviate from convergence to the Maastricht criteria. The model generates alternative fiscal policy regimes-allowing for regime shifts-depending on country characteristics and EU policies.